Excess body mass index‐ and waist circumference‐years and incident cardiovascular disease: The CARDIA study. (9th March 2015) - Reis, Jared P.; Allen, Norrina; Gunderson, Erica P.; Lee, Joyce M.; Lewis, Cora E.; Loria, Catherine M.; Powell‐Wiley, Tiffany M.; Rana, Jamal S.; Sidney, Stephen; Wei, Gina; Yano, Yuichiro; Liu, Kiang
Abstract : Objective: To determine the influence of the total cumulative exposure to excess overall and abdominal adiposity on the incidence of cardiovascular disease (CVD). Methods: Prospective study of 4, 061 white and black adults without CVD at baseline in 1985‐1986 (age 18‐30 years) from the multicenter, community‐based CARDIA study. Time‐varying excess body mass index (BMI)‐ and waist circumference (WC)‐years were calculated as products of the degree and duration of excess overall (BMI ≥ 25 kg/m 2 ) and abdominal adiposity [WC >94 cm (men) and >80 cm (women)], respectively, collected at up to eight examinations. Results: During a median of 24.8 years, there were 125 incident CVD, 62 coronary heart disease (CHD), and 33 heart failure (HF) events. Adjusted hazard ratios for CVD, CHD, and HF for each additional 50 excess BMI‐years were 1.20 (1.08, 1.34), 1.25 (1.07, 1.46), and 1.45 (1.23, 1.72), respectively. For each 50 excess WC‐years, these hazard ratios were 1.10 (1.04, 1.18), 1.13 (1.03, 1.24), and 1.22 (1.11, 1.34), respectively. Akaike information criterion values were lowest in models containing time‐varying excess BMI‐ or WC‐years compared to those including time‐varying BMI or WC only. Conclusions: Excess BMI‐ and WC‐years are predictors of the risk of CVD and may provide a better indicator of the cumulative exposure to excess adiposity than BMI or WC only.